2022
DOI: 10.1111/sms.14167
|View full text |Cite
|
Sign up to set email alerts
|

Individual responsiveness to a school‐based karate intervention: An ancillary analysis of a randomized controlled trial

Abstract: Introduction: School-based sport interventions have shown beneficial effects on psychosocial functioning and academic performance in children. However, the inter-individual variability in response to these types of interventions remains unclear. We aimed to determine which children benefit most from a school-based sport intervention. Methods: This is an ancillary analysis of a randomized controlled trial assessing the effects of a 1-year school-based karate intervention (versus "traditional" physical education… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…However, it is necessary to ensure the safety of martial arts classes and their appropriateness to the age characteristics of the students [15]. Our findings are consistent with previous studies that confirm the importance of physical activity in the daily lives of children and adolescents [9,16]. The sedentary lifestyle characteristic of distance learning is a serious issue, and our data underline the need to improve methods of stimulating physical activity among students [17].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, it is necessary to ensure the safety of martial arts classes and their appropriateness to the age characteristics of the students [15]. Our findings are consistent with previous studies that confirm the importance of physical activity in the daily lives of children and adolescents [9,16]. The sedentary lifestyle characteristic of distance learning is a serious issue, and our data underline the need to improve methods of stimulating physical activity among students [17].…”
Section: Discussionsupporting
confidence: 90%
“…Activities such as martial arts can improve children's executive functions, enhance motor skills, and create a suitable environment for teenage engagement [6,7,8]. School sports activities are particularly effective for children with psychosocial difficulties and low academic performance [9]. Martial arts classes increase the level of physical fitness in children and teenagers and teach the basics of self-defense [10].…”
Section: Introductionmentioning
confidence: 99%
“…The positive effects of karate training are indicated by the results of a study by Stamenković et al [14], Pinto-Escalona et al [15], Rutkowski et al [16]. Thus, the authors concluded that martial arts programs are useful for improving the physical fitness of school-age children, especially in such parameters as cardiorespiratory endurance, speed, agility, strength, flexibility, coordination and balance [14]; it is noted that better results were observed among children with normal body weight compared to children with overweight or obesity [16]; indicates that school sports karate is particularly effective for children with psychosocial difficulties and low academic performance [15].…”
Section: Introductionmentioning
confidence: 91%